Disinfection of cell-associated and extracellular HIV-1 by PUVA treatment - Deichmann, Martin; Sczakiel, Georg; Haas, Rainer (Journal of virological methods, 1997)
To inactivate cell-associated and extracellular HIV-1 while preserving cellular surface antigens, a procedure was used based on PUVA treatment i.e. addition of psoralen to cell suspensions followed by irradiation with UVA light. T-lymphoid MT-4 cells were infected with HIV-1 strain NL4-3, 4′-aminomethyl-4,5′,8-trimethylpsoralen was added, and the cell suspension was irradiated with 20 mW/cm2 UVA light for 3, 4 and 5 min. To evaluate virus inactivation, cells and supernatants were diluted serially and cocultured with uninfected MT-4 cells. Infectious HIV-1 was detected by cytopathic effects, immunofluorescence and p24 antigen ELISA. UVA irradiation at 3.6 J/cm2 (3 min 20 mW/cm2) reduced the amounts of both cell-associated and extracellular infectious HIV-1 by more than five orders of magnitude. Even at more stringent conditions of PUVA treatment (10 min 20 mW/cm2 UVA irradiation), conformational cellular surface epitopes remained detectable by flow cytometry.